CURRENT METHODS OF AMBULATORY ELECTROCARDIOGRAM MONITORING. TECHNICAL ASPECTS - E. V. Pervova (Klinicist)
The review considers the main characteristics and diagnostic capabilities of current noninvasive and invasive methods of ambulatory electrocardiogram monitoring used in diagnosis of cardiac rhythm and conduction disturbances. Strength and weaknesses of different methods of long-term electrocardiogram monitoring are discussed.